Leaching and mass transfer characteristics of elements from ion-adsorption type rare earth ore - Xiao, Yan-Fei; Feng, Zong-Yu; Hu, Gu-Hua; Huang, Li; Huang, Xiao-Wei; Chen, Ying-Ying; Li, Ming-Lai (Rare metals, 2015)
The differences in the leaching and mass transfer characteristics of ion-adsorption type rare earth ore between rare earth and non-rare earth impurities were investigated. It is determined that the leaching kinetics of rare earths （REs）, Mg and Ca could be described by the shrinking-core model. The leaching rate is controlled by inner diffusion and is in the order of Mg 〉 Ca 〉 RE. The apparent activation energy is 8.48, 6.79 and 6.32 kJ·mol^-1, respectively. In leaching system of Al, the leaching efficiency decreases with the increase in temperature because of hydrolysis reactions. The leaching efficiency of aluminum increases firstly and then decreases with the passage of time when the temperature is higher than 35 ℃. Besides, there is a good consistency in leaching characteristics and mass transfer, and the order of the time-to- peak is Mg 〈 Ca 〈 RE 〈 Al. Therefore, rare earth and non-rare earth may be partly separated by expanding the separation coefficient. The research could provide a theoretic basis for the separation of rare earth and non-rare earth impurities. Furthermore, compound leaching with magnesium salt and calcium salt is innovatively proposed to solve the problem of calcium and magnesium nutrient loss in the soil as well as eliminate ammonia-nitrogen emissions from the source.